Eksplorasi Transformasi Keuangan Digital Mahasiswa di Era Cashless Society - Puji Muniarty; M Rimawan; Ovriyadin Ovriyadin; M Syukur Dwiriansyah (Politeknik Ganesha Medan, 2026)
This study examines the changes in digital finance among college students in the cashless society era, where the use of GrabFood and the online transaction platform OVO is increasing in daily activities. This study uses a qualitative method with a phenomenological approach through interviews with five students active in the odd-even semester of the 2025/2026 academic year who use digital financial services using GrabFood to pay via OVO more than 5 times, as well as Generation Z born between 1997 and 2012. The results show that digital finance makes transactions easier and faster, but also encourages increased consumption and more spontaneous shopping decisions due to easy access and numerous promotions. On the other hand, the use of this system also provides benefits in the form of neater, more transparent, and easier to monitor financial records. In general, the transformation of digital finance not only changes the way students transact, but also influences their mindset and consumption habits. Therefore, digital financial literacy is crucial for students to manage their finances more wisely amidst increasingly rapid technological developments.